Is it really all about money? A study on incentives in elite team sports - Maier, C.; Woratschek, H.; Ströbel, T.; Popp, B. (European Sport Management Quarterly, 2016)
Research question: A key task for sports managers of elite sports clubs is to create an ideal environment that enables athletes to perform at their best. Therefore, we investigate the relationship among monetary incentives, organizational support, and athletic performance in elite team sports.